Bridging SoTL and Open Educational Resources/Practices (OER/P) Through Tagore’s Southern Theory in the Era of a Pandemic - Bayaga, Anass (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2022)
In recent times, while Scholarship of Teaching and Learning (SoTL) and pedagogy enabled by open educational resources/practices (OER/P-enabled pedagogy) have become paramount in higher education, both have hardly been addressed jointly. Given that both aim to adopt, share, and reuse open resources by lecturers and their students in higher education institutions, it would have been expected that both are conjointly used to enhance student learning instead of being used separately. Additionally, while studies are ongoing from different theoretical stances, SoTL and OER/P-enabled pedagogy research are considered separately. Consequently, and through systematic review, the current study aims at bridging SoTL and OER/P-enabled pedagogy through Tagore’s southern theory in the era of a pandemic in the educational setting.Tagore’s southern theory can demonstrate and explain the tacit linkage between SoTL via OER/P. Accordingly, Tagore’s southern theory should be used in broadening and deepening our understanding and thus serve as a guiding principle to approach SoTL and OER/P-enabled pedagogy conjointly. One key implication is that while it is important to conceptualize the global design of teaching and learning, it is vitally important to take account of local histories. Thus, the culturally entrenched connotations and interpretations for inclusive education can be addressed by employing both SoTL and OER/P-enabled pedagogy simultaneously. The hope is that the research assists in grounding the future of SoTL via OER/P-enabled pedagogy exploration.